New species in the family Graphidaceae (Ascomycota: Ostropales) from the Philippines - Joshi, Santosh; Upreti, Dalip K.; Bawingan, Paulina A.; Hur, Jae-Seoun (Phytotaxa, 2018)
In the present paper three new species viz. Thalloloma nitidum, Thelotrema isidiosum and T. megasporum belonging to lichen family Graphidaceae are described from the Philippines and compared with the closely related taxa.